Exploring the experiences of Filipino single fathers: A qualitative study - Diesta, Ma. Angelica Christine A. (Animo Repository, 2018)
The purpose of this research is to explore the lived experiences of eight (8) Filipino single fathers. The researcher used a qualitative research design, particularly a multiple case study design to explore the present study. Findings revealed that Filipino Single Fathers in this study went through stages and transitions in relation to the post-divorce and bereaved life cycle based on the family systems theory. Five themes emerged in this study which are(1) Filipino Single Fathers in this present study experienced extreme stress due to the transition from being married to becoming single, (2) Feelings of inadequacy surfaced in performing the role of the mother and father in the household, (3) The participants reported that they developed stronger and positive bond with their children, (4) Single Fathers in this present study looked for support groups in helping them cope with the sudden change in their life, (5) A heightened spirituality was observed by single fathers in this study. This research points to a new understanding of the experiences of Filipino Single Fathers. Results were discussed in the light of how counseling single fathers may be better improved.